2022
DOI: 10.1016/j.jgr.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Jinan Red Ginseng and licorice extract mixtures ameliorates nonalcoholic steatohepatitis by modulating lipogenesis

Abstract: Background Nonalcoholic steatohepatitis (NASH) is one of the main chronic liver diseases. NASH is identified by lipid accumulation, inflammation, and fibrosis. Jinan Red Ginseng (JRG) and licorice have been widely used because of their anti-inflammatory and hepatoprotective effects. Hence, this study assessed JRG and licorice extract mixtures' effects on NASH progression. Methods Palmitic acid (PA) and the western diet (WD) plus, high glucose-fructose water were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“… 103 Previous reports have shown that hyperactivation of SREBP-1c promotes hepatic TG accumulation, 104 , 105 suggesting that targeting SREBP-1c for regulating hepatic lipid metabolism might be an appropriate strategy for NASH treatment. 105 , 106 Oltipraz (OPZ) is a synthetic dithiolethione with an antisteatotic effect by inhibiting the activity of LXR-α, thereby suppressing SREBP-1c activity. 107 Administration of the thiol-reactive agent OPZ significantly attenuated the progression of histologic abnormalities, especially hepatic fibrosis in rats on a CDAA diet.…”
Section: Signaling Pathways Driving Nafl/nash Development and Related...mentioning
confidence: 99%
“… 103 Previous reports have shown that hyperactivation of SREBP-1c promotes hepatic TG accumulation, 104 , 105 suggesting that targeting SREBP-1c for regulating hepatic lipid metabolism might be an appropriate strategy for NASH treatment. 105 , 106 Oltipraz (OPZ) is a synthetic dithiolethione with an antisteatotic effect by inhibiting the activity of LXR-α, thereby suppressing SREBP-1c activity. 107 Administration of the thiol-reactive agent OPZ significantly attenuated the progression of histologic abnormalities, especially hepatic fibrosis in rats on a CDAA diet.…”
Section: Signaling Pathways Driving Nafl/nash Development and Related...mentioning
confidence: 99%
“…Jinan red ginseng (JRG), another type of KRG produced at Jinan, Jeollabuk-do, was reported to play a pharmacological role in NASH by modulating lipogenesis in mice and hepatocytes. JRG reduced the palmitic acid (PA)-induced lipotoxicity, inflammation, and oxidative stress in hepatocytes and macrophages [ 43 ]. JRG also decreased the expression of NASH-associated genes in hepatocytes and macrophages [ 43 ].…”
Section: Pharmacological Roles Of Ginseng and Ginsenosides In Nashmentioning
confidence: 99%
“…21 Another study showed that a combination of Jinan red ginseng and sweetgum was effective in reducing NASH adipogenesis by modulating AMPK downstream signaling pathways. 22 It is proven that ginsenoside Rk3 improves liver function by lowering serum inflammatory factor levels, reducing inflammatory stress, and recovering the anti-oxidant balance of liver tissue. 20 Never-theless, the preventive effect of ginsenoside Rk3 against NASH…”
Section: Introductionmentioning
confidence: 99%
“…Panax ginseng saponins are the major active ingredients of ginseng and are involved in the regulation of antioxidant, anti-inflammatory, and anti-tumor pathological processes. , Ginsenoside Rk3 is among the rarely found saponins in the triol group of saponins and has been reported to have physiological effects including antidiabetic, anticancer, and anti-alcoholic fatty liver. Ginsenosides have been reported to inhibit inflammatory infiltration of the liver parenchyma and improve the progression of NAFLD . Another study showed that a combination of Jinan red ginseng and sweetgum was effective in reducing NASH adipogenesis by modulating AMPK downstream signaling pathways . It is proven that ginsenoside Rk3 improves liver function by lowering serum inflammatory factor levels, reducing inflammatory stress, and recovering the anti-oxidant balance of liver tissue .…”
Section: Introductionmentioning
confidence: 99%